Clinical Profile of Patients Presenting with Corneal Foreign Bodies: A Cross-Sectional Study Conducted in a Tertiary Hospital in Nepal - Shrestha, Tina; Parajuli, Sanket; Sharma, Sadhana; Shrestha, Riyaz; Singh, Prerana (Nepalese Journal of Ophthalmology, 2022)
Introduction: Corneal foreign bodies are one of the commonest forms of ocular trauma, the majority of which occur due to occupational exposure. The aim of this study was to study the profile of patients with corneal foreign bodies. Materials and methods: A hospital based prospective study was conducted among 60 patients presenting to the ophthalmology outpatient department in Dhulikhel Hospital-Kathmandu University Hospital (DH-KUH) over a time span of 6 months. Demographic data of patients, clinical characteristics of foreign bodies and associated complications were noted. Results: Most of the patients were males (n=55) belonging to the 21-30 age group (n=24). Majority of them were workers in metal industries (n=26). Welding and cutting metal were implicated as the most common mode of injury (n=53). Conclusion: By virtue of this study, we identified the high risks associated with sustaining this form of ocular trauma. The incidence and hence the prevalence of corneal foreign body can be gradually levelled down if we aware the people about the associated complications and advise them to use protective eye wears (PEW).